Coronavirus disease 2019 (COVID-19) and the risk of hypertensive disorders of pregnancy: a retrospective cohort study - Michael Baracy; Fareeza Afzal; Susanna M Szpunar; Makenzie Tremp; Karlee Grace; Marina Liovas; Muhammad Faisal Aslam (Taylor & Francis Group, 2021)
Objective: To evaluate of COVID-19 disease in pregnant women and its association with hypertensive disorders of pregnancy. Design: Retrospective Cohort Study Setting: Multicenter study from a large metropolitan hospital system Methods: Patients who tested positive for COVID-19 during their pregnancy and delivered were compared to the three subsequent deliveries of patients who tested negative (controls). We evaluated the impact of COVID-19 on the development of hypertensive disorders of pregnancy. Results: Compared with pregnancies negative for SARs-CoV-2 infection, maternal SARs-CoV-2 infection was associated with an increased risk for hypertensive disorders of pregnancy (OR 3.68, 95% CI 1.67 − 8.10). Tweetable Abstract Patients who test positive for COVID-19 during their pregnancy are at increased risk of developing a hypertensive disorder of pregnancy. Earlier SARs-CoV-2 infection results in an increased risk of developing a hypertensive disorder.